2014
DOI: 10.1002/lt.23969
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-based scores do not predict post-transplant recurrence of hepatocellular carcinoma in patients within milan criteria

Abstract: Increased preoperative inflammation scores, such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and inflammation-based index (IBI) have been related to post-transplant HCC recurrence. We evaluated the association between inflammation-based scores (NLR, PLR, IBI) and post-LT HCC recurrence as well as tumor necrosis after transarterial embolization. 150 consecutive patients who underwent transplantation for HCC within the Milan criteria between 1996 and 2010 were included; data regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 30 publications
(84 reference statements)
3
39
1
Order By: Relevance
“…No inflammation-based scores, including PLR, were superior to preoperative PLT, in agreement with a previous study. (20) In particular, the significance of PLR despite the insignificance of neutrophil, lymphocyte, and NLR supports the dominant importance of platelets per se. In contrast to the surrogate markers, platelets are effector cells that directly interact with cancer cells in the metastatic cascade (4)(5)(6)(7)10,11) ; thus, their association with tumor recurrence appears to be robust and independent in liver transplant recipients whose systemic inflammation status and PLTs are both affected by liver disease.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…No inflammation-based scores, including PLR, were superior to preoperative PLT, in agreement with a previous study. (20) In particular, the significance of PLR despite the insignificance of neutrophil, lymphocyte, and NLR supports the dominant importance of platelets per se. In contrast to the surrogate markers, platelets are effector cells that directly interact with cancer cells in the metastatic cascade (4)(5)(6)(7)10,11) ; thus, their association with tumor recurrence appears to be robust and independent in liver transplant recipients whose systemic inflammation status and PLTs are both affected by liver disease.…”
Section: Discussionmentioning
confidence: 91%
“…(20) Definition and cutoff value of the inflammation-based scores were determined in previous research. (20) After matching, all analyses were performed by accounting for clustering within the matched pairs and weighting by nonfixed matching ratio. Baseline characteristics were analyzed using clustered linear modeling (continuous variables) or the Cochran-Mantel-Haenszel test (categorical variables).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of PIVKA-Ⅱ and AFP provided increased accuracy than any of them alone [53] . Other biomarkers related to systemic inflammation such as neutrophilto-lymphocyte ratio, platelet-to-lymphocyte ratio and inflammation-based index have been associated with poor survival in HCC [54,55] , but their role in predicting HCC recurrence after LT is controversial [29,56,57] , probably because these parameters are highly influenced by after the liver biopsy [31] casts doubts on recommending this procedure to all patients with HCC before LT. Unfortunately the Toronto criteria have not been validated in independent cohorts.…”
Section: Namentioning
confidence: 99%
“…In contrast, Parisi et al reported the negative predictive role of PLR and NLR in HCC patients receiving liver transplantation [31], which appears that inflammatory markers do not have a predictive role in smaller tumor. One of reasons was the careful selection of transplantation candidates and strict adherence to the Milan criteria in this report.…”
Section: Discussionmentioning
confidence: 89%